2012
DOI: 10.1097/igc.0b013e31824ff142
|View full text |Cite
|
Sign up to set email alerts
|

Early Invasive Cervical Cancer During Pregnancy

Abstract: Diagnosis of cervical cancer can occur during pregnancy. Different options of fertility-sparing treatment can be discussed on the basis of several factors: tumor stage, gestational age, and the patient's desire regarding fertility and pregnancy sparing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 33 publications
(45 reference statements)
0
7
0
1
Order By: Relevance
“…Further studies have confirmed the safety of less radical surgery in non-pregnant women [ 22 , 23 ]. However, reports have concluded that 1 of 7 (14.3%) cases treated with vaginal radical trachelectomy during pregnancy have resulted in early abortions [ 24 , 25 ]. Ideally, future prospective studies should be carried to validate these findings.…”
Section: Discussionmentioning
confidence: 99%
“…Further studies have confirmed the safety of less radical surgery in non-pregnant women [ 22 , 23 ]. However, reports have concluded that 1 of 7 (14.3%) cases treated with vaginal radical trachelectomy during pregnancy have resulted in early abortions [ 24 , 25 ]. Ideally, future prospective studies should be carried to validate these findings.…”
Section: Discussionmentioning
confidence: 99%
“…Further studies have con rmed the safety of less radical surgery in non-pregnant women [22,23] . However, reports have concluded that 1 of 7 (14.3%) cases treated with vaginal radical trachelectomy during pregnancy have resulted in early abortions [24,25] . Ideally, future prospective studies should be carried to validate these ndings.…”
Section: Discussionmentioning
confidence: 99%
“…That is why decisions have to be taken by a multidisciplinary team of obstetricians, neonatologists, gynaecologists oncologists, medical oncologists, and pathologists not only in such cases but also in the rest of fertility treatment preservations cases similar to our case. One should always take into account what the patient wants and keeping her opinion central to taking decisions [ 11 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Pregnancy does not appear to accelerate the natural history of the tumour or increase the incidence of metastatic disease, although thanks to early diagnosis, the survival rate of patients diagnosed during pregnancy seems somewhat higher than in women who are not pregnant. On the contrary or when there is a late diagnosis, there does seem to be a worse prognosis, partly because of therapeutic limits in these specific cases [ 10 – 11 ].…”
Section: Introductionmentioning
confidence: 99%